2020
DOI: 10.13057/biodiv/d211027
|View full text |Cite
|
Sign up to set email alerts
|

Maximum entropy modeling for the conservation of Hopea odorata in riparian forests, central Thailand

Abstract: Abstract. Asanok L, Kamyo T, Marod D. 2020. Maximum entropy modeling for the conservation of Hopea odorata in riparian forests, central Thailand. Biodiversitas 21: 4663-4670. Hopea odorata plays a dominant role in both ecologically and economically in Thailand. We analyzed potentially suitable areas for H. odorata in the riparian zone of the Chao Phraya River using the software MaxEnt. Modeling included 164 occurrence records along with 19 climate-related variables, slope, aspect, and elevation. Precipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Following, land use, forest cover and soil variables showed to be consistent with previous studies suggesting that elevation was one of the most important environmental variables determining plant distribution such as Dipterocarpus alatus and Hopea odorata (Asanok et al 2020). On the one hand, topographical variables derived from DEM such as slope and aspect can show a positive correlation with the elevation variable (Evcin et al 2019).…”
Section: Evaluations Of the Model And Its Importancesupporting
confidence: 90%
“…Following, land use, forest cover and soil variables showed to be consistent with previous studies suggesting that elevation was one of the most important environmental variables determining plant distribution such as Dipterocarpus alatus and Hopea odorata (Asanok et al 2020). On the one hand, topographical variables derived from DEM such as slope and aspect can show a positive correlation with the elevation variable (Evcin et al 2019).…”
Section: Evaluations Of the Model And Its Importancesupporting
confidence: 90%
“…Meanwhile, Zhang et al (2018) stated climatic factors are very important in affecting plant regeneration, growth, and spread. A study by Asanok et al (2020) reported habitat suitability modeling indeed helps to improve understanding of the relationship between plants and respective habitats through incorporating the current location, microclimate, topographical, and edaphic factor data.…”
Section: Model Performancesmentioning
confidence: 99%
“…This study is the first to create a map of the habitat suitability model for B. angulata in Kalimantan using MaxEnt. Species distribution modeling (SDM) provides highly significant information for cultivation as well as conservation management, and shows the relationship between species as well as habitat by combining data on presence, microclimate, topography, and edaphic factors (Asanok et al 2020). Furthermore, SDM also provides information on environmental factors with the most influence on species distribution.…”
Section: Predicted Current Potential Distributionmentioning
confidence: 99%
“…Moreover, both species are dipterocarps (Dipterocarpaceae) that dominate the floodplain forests along the Chao Phraya River [14]. The distribution of these two species is determined by precipitation [45,46], as they are often dominant in tropical forests in Southeast Asia where high rainfall is a limiting factor [47]. Historically, both species were severely reduced by urbanization and were once only found in small forest patches and as isolated individuals along the Chao Phraya River [14].…”
Section: Species Composition Of Large Treesmentioning
confidence: 99%
“…Dominant species, such as Dipterocarpus alatus and Hopea odorata, were found in all cities, particularly in Lop Buri and Prathum Thani, respectively. A previous study reported that the upper and lower parts of the Chao Phraya River are suitable environments for populations of Dipterocarpus alatus and Hopea odorata, respectively [45,46]. The key limiting factors for these two species are distance from the sea, urbanized areas, and rainfall [14].…”
Section: Unique Speciesmentioning
confidence: 99%